2008
DOI: 10.1073/pnas.0806669105
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex neurons as a common target for classic and glutamatergic antipsychotic drugs

Abstract: Until recently, all known antipsychotic drugs were thought to block the dopamine D2 receptor. New evidence that agonists of the metabotropic glutamate 2/3 (mGlu2/3) receptors ameliorate psychotic and affective symptoms of schizophrenia suggests that compounds with different molecular targets may act on a common cellular target to treat schizophrenia. We hypothesized that normalizing the activity of neurons in the orbitofrontal cortex (OFC), a region that is increasingly implicated in the pathophysiology of sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 52 publications
1
62
1
Order By: Relevance
“…Reversal of PCP-induced motor hyperactivity was demonstrated for one of the first selective mGlu2/3 receptor agonists, LY354740 (Moghaddam and Adams, 1998), and was repeatedly confirmed for this and other mGlu2/3 receptor agonists in several laboratories (Cartmell et al, 1999). Various motor stereotypes induced by PCP-like drugs and 5-HT 2A agonists [(Ϯ)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane] are also readily inhibited by mGlu2/3 receptor stimulation (Gewirtz and Marek, 2000;Homayoun and Moghaddam, 2008).…”
Section: Mglu2/3 Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversal of PCP-induced motor hyperactivity was demonstrated for one of the first selective mGlu2/3 receptor agonists, LY354740 (Moghaddam and Adams, 1998), and was repeatedly confirmed for this and other mGlu2/3 receptor agonists in several laboratories (Cartmell et al, 1999). Various motor stereotypes induced by PCP-like drugs and 5-HT 2A agonists [(Ϯ)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane] are also readily inhibited by mGlu2/3 receptor stimulation (Gewirtz and Marek, 2000;Homayoun and Moghaddam, 2008).…”
Section: Mglu2/3 Receptor Agonistsmentioning
confidence: 99%
“…e Harsing et al, 2003Depoortere et al, 2005;Boulay et al, 2008;Singer et al, 2009. f Chan et al, 2008Homayoun and Moghaddam, 2008;Liu et al, 2008. NMDA receptor antagonists would preferentially block active NMDA channels in interneurons rather than pyramidal cells, resulting in a disinhibition of circuits.…”
mentioning
confidence: 99%
“…Recordings were made as described previously (28) while rats performed a behavioral task. Single units were isolated using Offline Sorter (Plexon) through a combination of manual and semiautomatic sorting techniques (44).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, mGluR5 is of current interest as a novel therapeutic target for the treatment of schizophrenia. Studies of mGluR5 positive allosteric modulators (PAMs) have repeatedly reported antipsychotic-like effects in rodent models of schizophrenia (see Vinson and Conn, 2012), which have been shown, in part, to be mediated through the frontal cortex (Homayoun and Moghaddam, 2008). Most interestingly, PAMs of mGluR5 reverse drug-induced negative and cognitive impairments in rodents, which are aspects of schizophrenia symptomatology mostly untreated by current therapeutics in a large percentage of patients.…”
Section: Mglur5 Binding Density and Protein Levels Are Unaltered In Tmentioning
confidence: 99%